Factors Affecting The Quality of Financial Reports: A Systematic Literature Review - Hasbullah, Hasbullah; Hidayah Tullah , Rahmad; Farhan, Reizy (Asosiasi Dosen Akuntansi Indonesia, 2023)
The quality of financial reports is the result of the process of accounting activities which can conclude the financial information used in making decisions. Financial reports must meet certain requirements to provide good financial reports. The purpose of this study is to determine the factors that influence the quality of financial statements. The method used is SLR (Systematic Literature Review). the Publish or Perish program is used to collect journal articles taken from the Google Scholar database to support research conducted. The articles collected are articles published with a period of 2018-2023, as many as 10 Scopus indexed international journal articles obtained from Google Scholar and Publish or Perish which are full text manuscripts and which can be accessed. Based on the results of the study, the factors that influence the quality of financial reports include accounting information systems, internal controls, country, religious status, gender, fixed assets, proof of ownership, information technology, application of accounting standards, human resources, culture, company size , age and psychological effect on the quality of financial reports